A European study on alcohol and drug use among young drivers: the TEND by Night study design and methodology - Siliquini Roberta; Piat Simone; Alonso Francisco; Druart Axel; Kedzia Marcin; Mollica Antonio; Siliquini Valeria; Vankov Daniel; Villerusa Anita; Manzoli Lamberto (BMC, 2010)
Abstract Background Young individuals are the age group with the highest risk of car accidents. One of main explanations relies on the use of psychoactive substances (alcohol, illegal and medicinal drugs), which are known to be major risk factors of road accidents, and whose consumption is almost universally more common among younger drivers. Although the correlation between psychoactive substances use and decrease in driving performance has been established in controlled experimental or laboratory settings, few studies were conducted in naturalistic circumstances. The TEND by Night project has been designed to evaluate the relationship between driving performance and psychoactive substances assumption in young drivers enrolled at typical places of consumption. Methods/Design The TEND by Night project, endorsed by the European Commission, is a multidisciplinary, multi-centric, cross-sectional study conducted in six European countries (Italy, Belgium/Netherlands, Bulgaria, Spain, Poland and Latvia). The study population consists of 5000 young drivers aged 16-34 years, attending recreational sites during weekend nights. The intervention is based on the portal survey technique and includes several steps at the entrance and exit of selected sites, including the administration of semi-structured questionnaires, breath alcohol test, several drug assumption test, and measurement of the reaction time using a driving simulator. The main outcome is the difference in reaction time between the entrance and exit of the recreation site, and its correlation with psychoactive substances use. As a secondary outcome it will be explored the relationship between reaction time difference and the amount of consumption of each substance. All analyses will be multivariate. Discussion The project methodology should provide some relevant advantages over traditional survey systems. The main strengths of the study include the large and multicentric sample, the objective measurement of substance assumption (which is typically self-reported), the application of a portal survey technique and the simultaneous evaluation of several psychoactive substances.